Wdrożenie czy reorganizacja - jak skutecznie zarządzać informatyczną infrastrukturą przedsiębiorstwa? - Seidel, Bartłomiej (Implementation or Reengineering - Looking for an Effective Way of Applying Information Technology into Business Processes, 2006)
A lot of well known errors and limitations still take place while implementing sophisticated information systems in Polish companies. On the other hand scientist and experts propose many new ways of managing information system development. What conclusion can be drawn out of comparison of this two phenomena?
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 511-518